2022
DOI: 10.3390/app12199616
|View full text |Cite
|
Sign up to set email alerts
|

Dry Printing of Ag–Ni Conductive Particles Using Toner-Type Printed Electronics

Abstract: Printed electronics are a set of additive manufacturing methods for creating future flexible electronics on thin polymeric sheets. We proposed the toner-type, dry, page-printing of Ag–Ni composite conductive particles on flexible plastic sheets without pre-treatment. No chemical solvents are necessary to compose the inks of the electronic materials used for the toner-type printing, and no chemical treatment is required for the plastic film substrate surface. In addition, multilayer printing is simple when usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Figure 1a shows the developer consisting of Ag nanoparticles (NPs) and carrier particles [85,86]. The carrier particle comprises the ferrite material and has a role in generating electrical charge in the toner particle by frictional charging and by prohibiting natural aggregation of the toner particle.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 1a shows the developer consisting of Ag nanoparticles (NPs) and carrier particles [85,86]. The carrier particle comprises the ferrite material and has a role in generating electrical charge in the toner particle by frictional charging and by prohibiting natural aggregation of the toner particle.…”
Section: Methodsmentioning
confidence: 99%
“…The dark gray particles include approximately 10% Ag NPs and 90% carrier particles by weight, and the mixed powder had sufficient fluidity for the developer particles. The fluidity of the developer particles is essential for drawing high-resolution electronic circuits, which are evaluated using the repose angle [85]. Figure 1b shows the SEM image of the developer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The second challenge is that achieving low resistivity and long-term stability of ink-based printed Cu lines is extremely difficult since Cu easily oxidizes into copper oxide (CuO) and cuprous oxide (Cu 2 O) when exposed to the air. Some studies have suggested the use of stabilizing agents such as polyvinylpyrrolidone (PVP) in synthesizing Cu nanoparticles (CuNPs) to protect them from oxidation. Additionally, while electronics printing on-demand in rugged environments can be used for lunar surface and deep space exploration missions, many inks have stability concerns such as short shelf lives, intolerance to vibrations, or variable G loads and need to be stored at a low temperature and then printed at higher temperatures. Finally, the use of environmentally unfriendly chemicals in inks, the highly tailored ink formulation requirements that are demanding in terms of time and cost, the inherent ink instabilities, and the required postprocessing thermal treatments to remove solvents/additives have all driven the need for alternative dry printing technologies. , To address these challenges, we have recently developed a novel additive nanomanufacturing (ANM) technique that allows on-demand nanoparticle generation by in situ laser ablation and real-time laser sintering processes. , …”
Section: Introductionmentioning
confidence: 99%